2015
DOI: 10.3390/ijerph120302749
|View full text |Cite
|
Sign up to set email alerts
|

Method Comparison for Enhanced Recovery, Isolation and Qualitative Detection of C. jejuni and C. coli from Wastewater Effluent Samples

Abstract: Seeking a sensitive protocol, culture-dependent methods were compared to detect thermophilic Campylobacter species in untreated urban effluents. We evaluated various combinations of selective media, with and without an enrichment steps, as well as an extra filtration step. Culture-independent real-time quantitative PCR was also included and all detected isolates underwent antimicrobial susceptibility testing. All tested water samples contained Campylobacter DNA, but only 64% were positive after culture. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Increase in tetracycline resistance has been reported to emerge from the extensive use of these antibiotics as prophylaxis and therapy of human and animal infections and in promoting animal growth [77]. Thus, Campylobacter resistance to tetracycline has been frequently reported in humans, animals and aquatic environments [78,79,80]. The current study observed a resistance rate of 32% of clinical Campylobacter isolates to tetracycline and 55% from water isolates.…”
Section: Discussionmentioning
confidence: 55%
“…Increase in tetracycline resistance has been reported to emerge from the extensive use of these antibiotics as prophylaxis and therapy of human and animal infections and in promoting animal growth [77]. Thus, Campylobacter resistance to tetracycline has been frequently reported in humans, animals and aquatic environments [78,79,80]. The current study observed a resistance rate of 32% of clinical Campylobacter isolates to tetracycline and 55% from water isolates.…”
Section: Discussionmentioning
confidence: 55%
“…However, Premarathne et al [80] recorded that the favored environmental place for Campylobacter spp. is to be the intestinal tract of most of birds and mammals; Ugarte-Ruiz et al [81] recorded that survival of Campylobacter spp. in surface water for a higher recovery of the organism in wide range of water quality changes.…”
Section: Discussionmentioning
confidence: 99%
“…Human samples (n = 152; 118 C. jejuni and 34 C. coli) were associated with campylobacteriosis cases in hospitals in the regions of Castilla y Leon, Extremadura and Andalucía between 2013 and 2016. Campylobacter isolates of urban effluent origin (n = 53; 6 C. jejuni and 47 C. coli) were collected from the wastewater treatment plants in the city of Madrid (Spain) between 2011 and 2013 (Ugarte-Ruiz et al, 2015). All isolates were obtained using culture based methods (Moreno et al, 2000;Ugarte-Ruiz et al, 2015;Hormeño et al, 2016) and speciated as C. jejuni or C. coli using a conventional multiplex PCR as previously described (Ugarte-Ruiz et al, 2012).…”
Section: Dna Extraction Genome Sequencing and Archivingmentioning
confidence: 99%